EDUCATION MANAGEMENT IN GRADUATE ORIENTATION - Wirayudha, Rahmat; Wahyu, Wahyu; Effendi, Rustam (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
Education graduates are more unemployed than those who work or are not in accordance with what the world wants. This doesn't only occur to bachelor, but also to senior high school graduates, so the government responds to this by prioritizing an education system whose link-and-match outcome as workers. Bridging this, vocational school is one solution. Vocational High School (SMK) is an embodiment of the school system with a vocational form, with various departments that certainly respond to the diversity of the world of work available. Types of Vocational Schools in Indonesia are attached in Appendix I. In this study, researchers only focusing on Vocational School majoring in Pharmacy. As a vocational school, The Pharmacy Department required to produce eligible graduates according to the work field and industry standard. The standard should be applied to qualified of work field and industry demands, Education Management is needed, which includes Planning, Implementation, Evaluation, and Supervision in the education process in schools in such a way that the competencies, expertise, and skills of graduates are in accordance with the demands of the world of work and industry. schools rely on the rules of School-Based Management (SBM). As time goes by, As time goes by, parents of vocational students want their children's ability to continue into the next levels with good character, religious, and academics. The various demands try to be fulfilled by schools by implementing various activities using 8 national education standards as a reference, which are applied through the school-based education management concept. This study focuses on how each Planning, Implementation, Evaluation, and Supervision of Education Management at ISFI Pharmacy Vocational School and Husada Vocational High School Pharmacy Study Program, which processes through the application of 8 National Standards of Education in influencing graduate orientation